IMPLEMENTASI LITERASI MEMBACA DALAM PEMBELAJARAN BAHASA INDONESIA DI SDI TARBIYATUL ATHFAL SURABAYA - Nur Fadhilah Safiyanti; Rudi Umar Susanto; Afib Rulyansah; Akhwani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of reading literacy in Indonesian language learning at SDI Tarbiyatul Athfal Surabaya, to identify teachers' efforts in improving students' reading literacy skills, and to analyze the supporting factors, inhibiting factors, and impact of reading literacy implementation on students. A qualitative approach with a descriptive research design was employed, involving the principal, classroom teachers, and students as research subjects. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing, while data credibility was ensured through source and time triangulation. The findings indicate that reading literacy has been implemented effectively through a 15-minute reading routine before lessons, read-aloud sessions, independent reading, discussion of reading content, and retelling activities integrated into Indonesian language learning. Teachers' efforts to enhance reading literacy included providing motivation, offering engaging reading materials, using varied instructional media, assisting students who experienced reading difficulties, and guiding students to comprehend texts. Supporting factors included the principal's support, the availability of a reading corner and reading materials, teachers' active role, and student enthusiasm, while inhibiting factors included differences in students' reading abilities, low reading interest among some students, limited reading habits at home, and a limited collection of reading materials. The implementation of reading literacy was found to positively affect students' reading interest, reading comprehension, vocabulary and knowledge acquisition, and critical thinking skills. Kata Kunci: Implementasi, Literasi Membaca, Pembelajaran Bahasa Indonesia, Sekolah Dasar